Have State Supreme Court Elections Nationalized?. (17th March 2021) - Weinschenk, Aaron; Baker, Mandi; Betancourt, Zoe; Depies, Vanessa; Erck, Nathan; Herolt, Quinne; Loehrke, Amanda; Makurat, Cameron; Malmberg, Hannah; Martell, Clarice; Novitzke, Jared; Riddle, Bradley; et al.
Abstract: Over the past several years, scholars of political behavior have become increasingly interested in the nationalization of U.S. elections. Research has shown that there is now a strong connection between presidential vote patterns and voting in House, Senate, gubernatorial, and state legislative elections. In this article, we extend previous research by examining the role of the presidential vote in state supreme court elections. Using an original dataset containing county-level election results (N = 15, 237) from 2000-2018 for all states that hold partisan or nonpartisan state supreme court elections, we examine the influence of presidential vote share in state supreme court elections. A number of important findings emerge. First, we find that presidential vote share influences voting in state supreme court contests. There is a statistically significant relationship in both partisan and nonpartisan elections even after controlling for incumbency, though the relationship is much stronger in states with partisan elections. Second, the relationship between presidential vote share and the state supreme court vote has been quite stable over time in states with partisan elections. Third, in states with states with nonpartisan elections, there has been some variability in the relationship between presidential and state supreme court voting patterns, although the data reveal an uptick in the strength of the relationship over time. Future research should continue to track the role of national political forces in state supreme court elections.